PENGARUH RASIO KATALIS ZEOLIT AKTIF/UMPAN PADA PROSES PIROLISIS LIMBAH SERBUK SAGU (Metroxylon sp) - Damayanti, Endah Dewi (Chem Info Journal, 2013)
Catalytic pyrolysis of waste starch powder using active zeolite catalyst has been carried out. The purpose of this study was to determine the ratio of catalyst/feed and compare the optimum catalyst containing compounds pyrolysis bio-oil yield. Catalyst characterization performed using X-ray diffraction and N2 gas adsorption. Bio-oil is produced characterized using Gas Chromatography-Mass Spectroscopy (GC-MS) to determine the content of compounds of pyrolysis bio-oil yield. As a result, the acidity of the active zeolite catalyst of 0.003 mol / g, the mineral content of the zeolite is mordenite and surface area, mean diameter and total pore volume of the catalyst amounted to 199.115 m2 / g, 20.55 Ã… and 66.1445 cc / g. Bio-oil produced at the optimum ratio of catalyst/feed 6% with the content of the compound is acetic acid with an abundance of 29.48%. The selectivity of zeolite catalysts active in the formation of compounds, namely methanol, acetone 2-propanone, and 2-furanone.